KERAGAMAN DAN POTENSI BIOMASSA TUMBUHAN BAWAH PADA HUTAN TANAMAN JATI (Tectona grandis L.f.) DI DESA LAMBAKARA KECAMATAN LAEYA KABUPATEN KONAWE SELATAN - Basrudin Basrudin; Sri Wahyuni (Universitas Haluoleo, 2017)
ABSTRACTThis study aims to determine the composition and diversity of understorey vegetation in Teak plantation at the Lambakara village, Laeya district, South Konawe and predict bigger biomassa and bottom botanical carbon trove on Teak plantation. This research was conducted at the Lambakara village, Laeya district, South Konawe, since September until November 2012. This study used a survey. Method a line transect by 0,01% intensity sampling was used in this research. there were 30 plots (2 m x 2 m) for analyzing vegetations. The results ofthe identification of plant species under the stands of teak found 24 species n 12 families. From the results of the study also note that from 24 plant species identified below there are 21 types of the non-legume plants and there are only 3 types of understorey legumes. The kind that has a density, frequency and importance value index of the highest type of Rumput Signal (Brachiaria decumbens) of the family Poaceae. Mastery level of plant species under the stands of Teak is low. Total value of diversity index(H’) under the stands of Teak plants are 1.036 (rich medium). Total carbon storage by plants under 0,0575 tonnesHa-1. Teak with 2 years have the highest carbon storage 0,008 tonnesHa-1. Keywords: Teak, understorey, diversity, Biomassa